2006
DOI: 10.1073/pnas.0602753103
|View full text |Cite
|
Sign up to set email alerts
|

Divergent mtDNA lineages of goats in an Early Neolithic site, far from the initial domestication areas

Abstract: Goats were among the first farm animals domesticated, Ϸ10,500 years ago, contributing to the rise of the ''Neolithic revolution.'' Previous genetic studies have revealed that contemporary domestic goats (Capra hircus) show far weaker intercontinental population structuring than other livestock species, suggesting that goats have been transported more extensively. However, the timing of these extensive movements in goats remains unknown. To address this question, we analyzed mtDNA sequences from 19 ancient goat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 32 publications
5
90
1
2
Order By: Relevance
“…To obtain a maximum value for the biomass of domesticated megafauna, I calculated the present proportion of human biomass to domestic stock biomass as tabulated by Hern (22). I then used that proportion to back-calculate the maximum biomass of domestic stock, given the estimated biomass of humans, going back to 10.5 kyr B.P., by which time pigs, goats, sheep, and cattle were first domesticated (31)(32)(33)(34)(35). For time slices up to 6 kyr B.P., only pigs, goats, and cattle were included in the domestic livestock count.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain a maximum value for the biomass of domesticated megafauna, I calculated the present proportion of human biomass to domestic stock biomass as tabulated by Hern (22). I then used that proportion to back-calculate the maximum biomass of domestic stock, given the estimated biomass of humans, going back to 10.5 kyr B.P., by which time pigs, goats, sheep, and cattle were first domesticated (31)(32)(33)(34)(35). For time slices up to 6 kyr B.P., only pigs, goats, and cattle were included in the domestic livestock count.…”
Section: Methodsmentioning
confidence: 99%
“…A study of ancient mtDNA has shown that two haplotypes of domestic goats (the A and C lineages) had arrived in southern France by 7,300 B.P., suggesting their dispersal out of the Near East as a single package (66). Among modern goat breeds in Portugal researchers have found both the ubiquitous A haplotype and the much more restricted haplotype C (67).…”
Section: The Diffusion Of Animal Domesticates In the Mediterranean Basinmentioning
confidence: 99%
“…Last but not least, ancient DNA conservation is highly dependent upon the environment, with arid zones being less favorable (Edwards et al 2004). Nevertheless, aDNA studies have addressed important questions, including the possible contribution of extinct wild populations to the modern domesticates' gene pool (Kimura et al 2010), and past diversity in domestic stock subsequently lost over their breeding history (Fernández et al 2006).…”
Section: Approaches To Diagnosing Domestication In Animalsmentioning
confidence: 99%
“…Luikart et al (2001) interpret this lack of phylogeographic patterning as reflecting the continual transport of goats through human commerce over their entire history as domesticates. However, more recently, Naderi et al (2008) noted that such diversity of mitochondrial DNA haplogroups is also compatible with a single domestication center, with a phase of human management of wild or semi-domesticated goat populations comprising multiple mtDNA lineages, before geographic dispersion and subsequently local extinction of some haplogroups (Fernández et al 2006). Y-chromosome haplotypes from 20 living populations indicate a common origin for goat patrilines in the Levant and Maghrebian coastal regions (Pereira et al 2009).…”
Section: Goatsmentioning
confidence: 99%